Viral Infection and Lung Cancer Immunotherapy - Kalinka, Ewa; Chmielewska, Izabela; Wojas-Krawczyk, Kamila (Frontiers in Oncology, 2021)
Immunotherapy with immune checkpoints inhibitors (mainly anti-PD1 and anti-PDL1 monoclonal antibodies) became a standard of care in non-small cell lung cancer (NSCLC) patients.1-10 Most of the clinical trials excluded patients with hepatitis B (HBV), hepatis C (HCV) and human immunodeficiency virus (HIV) active infection.1-10 Despite the progress in treatment of these infections, they remain an unresolved clinical problem when lung cancer immunotherapy should be initiated in an NSCLC patient. This manuscript summarizes the data from the literature concerning this subgroup of patients including the rationale for immunotherapy initiation depending the HBV, HCV or HIV infection status, the risk of adverse events and the efficacy compared to non-infected patients. One of the crucial questions is how the candidates to immunotherapy should be screened for HBV, HCV and HIV infections. The year 2020 brought the world a new but dynamic viral problem – severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2). The incorporation of known data in oncology guidelines became a burning need. Then, which group of the infected patients can be treated with immunotherapy despite the infection. Oncologists should also know if these patients should receive antiviral therapy and what are the safe combinations in these settings. We also indicate which of the adverse events should be monitored carefully during checkpoint inhibitors treatment.